New Data Hiding Approach Based on Biological Functionality of DNA Sequence - Abdullah A. Abdullah; Adel S. Eesa; Ahmed M. Abdo (Science Journal of University of Zakho, 2019)
Data hiding or steganography has been used ever since a secret message was needed to be transferred. Data hiding methods need a medium to be cover for secret message that is to be sent. Different mediums are used such as image, video, audio, and last decade the deoxyribose nucleic acid (DNA). In this paper, a new data hiding approach based on the DNA sequence is proposed. Unlike many existing methods, the proposed method does not change the biological functionality of the DNA reference sequence when the sequence is translated into amino acids. The proposed method is consisting of two steps: the first step is encrypting the message using the Toffoli quantum gate. The second step is embedding the encrypted message into DNA sequence by taking one codon at a time and considering amino acids' biological functionality during the embedding process. Experimental results show that the proposed method outperforms the existing schemes preserving biological functionality in terms of cracking probability, and hiding capacity for bit per nucleotide.